The European Parliament at the First Crusade - Enzo Cannizzaro (European Papers, 2019)
(Series Information) European Papers - A Journal on Law and Integration, 2019 4(2), 423-425 | Editorial | (Abstract) On 21 October 2019, in a piece published on Verfassungsblog, twenty-nine influential experts in European affairs have harshly rebuked the European Parliament for rejecting the nomination of Sylvie Goulard to the new European Commission (Fairness, Trust and the Rule of Law: Statement on the European Parliament's confirmation procedure concerning Sylvie Goulard, www.verfassungsblog.de). The European Parliament only narrowly elected Ms. von der Leyen President of the Commission. Various political groups were torn apart, between bowing to the European Council and the chaos that could have ensued had the European Parliament voted otherwise. The process of appointment of the other members was dotted by parliamentary skirmishes and manoeuvrings and some of the candidates were rejected by the European Parliament after informal hearings, among them Ms. Goulard. Far from being irreprehensible, thus, the unilateral choice of the future President of the Commission seems to have been inspired by the desire of the heads of State or Government of the Member States to re-take the full lead, at the expense of the European Parliament. By no means, however, this twist is a zero-sum game. In the complex institutional system of the EU, the loss of prestige, influence and power of one institution will hardly be compensated by the gain of another. The loss of influence of the European Parliament will fatally disturb the institutional balance, in such a way that it will be hard to recast it. If this is the first backlash of the populist wave in Europe, the process of the European integration is to have harsh days ahead.